Effects of silver sulfide nanoparticles on the microbial community structure and biological activity of freshwater biofilms. Issue 12 (31st October 2018) - Liu, Songqi; Wang, Chao; Hou, Jun; Wang, Peifang; Miao, Lingzhan; Li, Tengfei
Abstract : Silver sulfide nanoparticles influence physical properties, microbial community, and functional capacities of freshwater biofilms due to nanoparticles-specific effects. Abstract : Ensuring the safety of silver sulfide nanoparticles (Ag2 S NPs) is essential for their application in various fields. Here, we explored changes in the microbial community composition and biological activity of freshwater biofilms treated with Ag2 S NPs (0.2, 1, and 5 mg L −1 ) for 5 days. Our results indicated that the Ag2 S NPs significantly changed the physiological properties of the biofilms to different extents, e.g., increasing the amount of extracellular polymeric substances, enhancing the activity of antioxidant systems, and decreasing algal biomass. The microbial community structure was obviously changed; the predominant bacteria Phormidium dramatically decreased while Flavobacterium became the dominant genus, exhibiting different levels of resistance and tolerance for Ag2 S NPs. Moreover, changes in the functional capacities of biofilms, including photosynthesis potential and functional extracellular enzymes related to nutrient cycling, varied after Ag2 S NP exposure in a concentration-dependent manner. Our findings suggested that the harmful effects of Ag2 S NPs on aquatic ecosystems should be considered carefully.